The adjustability of the expatriate manager: proposal of an improved measurement scale - Waxin, Marie-France (2005)
The adjustability of expatriate managers has a major influence on the success or failure of their mission. Yet, because of the difficulty of measuring this antecedent, it does not always receive the attention that it deserves. The objective of this research is to propose an improved measurement scale of the six dimensions of expatriates' adjustability. We have simplified the measures of the first five dimensions of adjustability and have operationalized active stress resistance by creating an index based on Folkman et al. (1986)'s work. Our sample consisted of 224 managers, of which 54 were French, 53 German, 60 Korean and 57 Scandinavian. The respondents were expatriated in the area of New Delhi, India. In order to test the structure of our scale, we conducted principal components factor analyses on the complete sample and on the four cultural samples. Our research allowed us to propose an improved measurement scale of adjustability, a scale that comprises fewer items and that can be used more easily in researches on cross-cultural adjustment. We showed that the structure of the six dimensions of adjustability remained stable for the different countries of our research.